2010
DOI: 10.1002/humu.21354
|View full text |Cite
|
Sign up to set email alerts
|

A novel germline CDKN1B mutation causing multiple endocrine tumors: clinical, genetic and functional characterization

Abstract: Multiple endocrine neoplasia (MEN) syndromes are characterized by tumors involving two or more endocrine glands. Two MEN syndromes have long been known: MEN1 and MEN2, caused by germline mutations in MEN1 or RET, respectively. Recently, mutations in CDKN1B, encoding the cyclin-dependent kinase (Cdk) inhibitor p27, were identified in patients having a MEN1-like phenotype but no MEN1 gene mutations. Currently, the molecular mechanisms mediating the role of p27 in tumor predisposition are ill defined. We here rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
74
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(78 citation statements)
references
References 20 publications
3
74
0
1
Order By: Relevance
“…This finding has prompted us to search CDKN1B mutations in MEN1-and RETnegative patients showing a MEN-like phenotype in the human. To date, six germline mutations have been identified leading to the definition of a new type of MEN-like syndrome in the human, named MEN4, though the phenotypic features are still undefined due to the small number of patients reported (1,2,3,4,5). Most CDKN1B mutations reported so far associated with MEN4 syndrome are inactivating mutations that lead to prematurely truncated protein (TGGOTAG at codon 76 (p.W76X)) (4) or to a premature stop at codon 69 caused by a 19 bp duplication (2), to a protein predicted to be 60 amino acids longer due to a change in the stop codon (TAA to CAA; stop to Q) (3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding has prompted us to search CDKN1B mutations in MEN1-and RETnegative patients showing a MEN-like phenotype in the human. To date, six germline mutations have been identified leading to the definition of a new type of MEN-like syndrome in the human, named MEN4, though the phenotypic features are still undefined due to the small number of patients reported (1,2,3,4,5). Most CDKN1B mutations reported so far associated with MEN4 syndrome are inactivating mutations that lead to prematurely truncated protein (TGGOTAG at codon 76 (p.W76X)) (4) or to a premature stop at codon 69 caused by a 19 bp duplication (2), to a protein predicted to be 60 amino acids longer due to a change in the stop codon (TAA to CAA; stop to Q) (3).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic studies in the rats predisposed to MENX identified a loss-of-function germline mutation in the Cdkn1b gene that encodes the cyclin-dependent kinase (Cdk) inhibitor p27 as the causative mutation for the MENX syndrome (1). Subsequently, mutations in the human homolog CDKN1B gene were identified in patients with multiple endocrine tumors that were negative for MEN1 or RET mutations (2,3,4). As a consequence of these observations, a novel human MEN-like syndrome, caused by germline mutations in CDKN1B, was recognized as a separate disease and denoted MEN4 (5).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, CDKN1B germline mutations have been described in multiple endocrine tumors (7). CDKN1B also harbors numerous polymorphisms that in several tumors have been variably associated with disease progression and patients' outcome (11)(12)(13)(14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, a MEN 1-like syndrome has recently been described and referred as MEN 4 (3,4). No mutations in CDKN1B have been found in 16 patients with a MEN 1 phenotype without MEN 1 mutations (5, 6), suggesting that CDKN1B germline mutations can predispose to the development of endocrine tumors in humans (3,4,7). A total of 21 single nucleotide polymorphisms in CDKN1B have also been described, 11 of which have low allelic frequency (5%) and 9 occur within the non-coding regions of the gene (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…A new mutation recognized is CDKN1B, which encodes cyclin dependent kinase p27. This mutation leads to development of multiple small intestinal neuroendocrine tumors [11]. …”
Section: Discussionmentioning
confidence: 99%